(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was to verify the effect of physical training on the levels of hemoglobin in athletes from professional football. Advances in the science of exercise have contributed significantly to the improvement in the performance of athletes. To get a good performance in football, we need a system buster well developed, refined through physical training, technical and games. The physical training alters the levels of the protein hemoglobin which is present in red blood cells and the main responsible for transporting oxygen in the body and can take up to an anemia of sport. The sample population and were composed of 13 athletes from professional football, aged between 19 and 38 years, with average age of 25 years. For collections of data was used to analyze blood (blood) achieved by athletes, pre and post the period of training and games, which were held during the season of 4 months. After analyzing the results, there was an increase in the hematocrit, which rose from 42.1% to 43.6%; The levels of hemoglobin, which were 13.9 g / dl and increased to 14.5 g / dl; and the amount of erythrocytes which fell from 4.71 to 4.93 millions /mm3 millions /mm3. From the results, we conclude that the physical training in football elevates the levels of hemoglobin in the blood, improving the transport system and oxygen uptake and the fitness that influences directly on the performance of athletes.